Estrategias de reproducción matrimonial de la élite económica en Chile - Huneeus, Sebastián (Revista de Sociología, 2013)
By means of twelve in depth interviews and discourse analysis, some of the objective and subjective conditions that explain the interpersonal affinity of the élite are described. The conclusions argue how the system of affinities is based upon marriage restrictions and preferences and, secondly, that there is a process of social closure and aperture that explains the structure of the partial renewal of this group.